Post Caesarean Caecal Perforation with Fecal Peritonitis - Yadav, M; Joshi, P; Koirala, P; Ghimire, S; Safi, S; Shrestha, I; Ojha, N; Amatya, A; Gurung, G; Rana, A (Nepal Journal of Obstetrics and Gynaecology, 2012)
NJOG 2011 Nov-Dec; 6 (2): 58-59 DOI: http://dx.doi.org/10.3126/njog.v6i2.6762